Environmental education and the use of medicinal plants used by the population of union district Bandeirante-Rondônia - Lima, Renato Abreu; Pires, Laiza Sabrina Santos; Vieira, Natan Gonçalves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The present study aimed to retrieve information about the use of medicinal plants used by the residents of the district of Union Bandeirante-RO, as well as its popular botanical used, their preparation and the correct identification of these plants. Also serve to spread the popular culture of the use of plants and their relation to Environmental Education. Dialogues were employed to direct the interview based on structured with open and closed questions questionnaire. In total, 70 residents were interviewed between 21 to 57 years, with different socio-cultural and occupational activity levels. The results show that 85% of respondents make use of medicinal plants and only 15% of them do not. 53 species of medicinal plants distributed in 34 botanical families the most cited were cited were Asteraceae with 29%, 24% Lamiaceae, Myrtaceae and Lauraceae of 19 and 14%, respectively. The most cited plants were: Brazil mint (Mentha arvensis L.) with 14 citations, Goiás Boldo (Vernonia condensata Baker) and lemon balm (Melissa officinalis L.) at 11, fennel (Foeniculum vulgare Mill.) With 6, chamomile (Chamomilla recutita (L.) Rauschert.) 5, guaco (Mykania glomerata Spreng), aloe (Aloe vera (L.) Burn.F) and garlic (Alliun sativum L.) with four citations. The form used most often cited by residents was the tea. In preparing the recipes, the sheet had the highest number of citing and the most cited indications were: antiflamatório, healing, soothing, diarrhea, flu. With respect to education by understanding environmentalist, the majority of respondents reported that it is understood as sensitizer to educate to raise awareness.